Mitigation of ICRF—edge plasma interaction in Alcator C-Mod - R. Diab; S.G. Baek; A.Q. Kuang; Y. Lin; E.S. Marmar; J.L. Terry; S.J. Wukitch; the Alcator C-Mod Team (Nuclear Fusion)
The parasitic interaction between ion cyclotron range of frequencies (ICRF) waves and the edge plasma has long limited high-power ICRF utilization in magnetically confined fusion plasmas. In this paper, we report on the successful mitigation of this interaction by power tapering a four-strap field-aligned (FA) antenna in the Alcator C-Mod tokamak. With the antenna operated in dipole phasing ( $0π0π$ ), the ratio of the power coupled by the central two straps ( $P_cent$ ) to the power coupled by the outer two straps was varied at fixed total coupled ICRF power ( $P_tot$ ). With $P_cent$ / $P_tot ≈ 0.8-0.9$ , no enhancement of the plasma potential was measured despite 1 MW of coupled ICRF power. When the antenna is powered, energy deposition increases on its four corners and on neighboring limiter tiles magnetically connected to some of those corners. The energy deposited on the antenna and limiter is minimized together with near-field plasma potentials. Additionally, we show that deviation from $P_cent$ / $P_tot ≈ 0.8$ enhances wave-plasma interactions in places not magnetically connected to the antenna. These far-field effects are correlated with changes in the antenna spectrum. Hence, on C-Mod, near-field and far-field interactions were minimized for about the same range of $P_cent$ / $P_tot$ . Optimal power tapering was also found to improve ICRF heating efficiency and facilitate H-mode access. Finally, we show that the heat flux pattern on the toroidally aligned antennas reverses with the direction of the RF-induced E × B flow in front of the antenna, a correlation not observed for the FA antenna. We argue that the RF-induced E × B flow, which carries high-density plasma from the near-SOL, is aligned with the FA antenna and does not intercept its corners, where the plasma potential is large. This could explain the previously reported smaller impurity generation by the FA antenna (Wukitch et al 2013 Phys. Plasmas 20 056117).